2012
DOI: 10.1128/mcb.06310-11
|View full text |Cite
|
Sign up to set email alerts
|

The Spt5 C-Terminal Region Recruits Yeast 3′ RNA Cleavage Factor I

Abstract: During transcription of protein-coding genes, RNA polymerase II (Pol II) associates with many factors, including elongation factors, RNA-processing factors, and chromatin-modifying enzymes (42,66,80). Many of these factors are recruited by binding to the C-terminal repeat domain (CTD), a tail-like extension of the largest Pol II subunit that is highly phosphorylated during elongation (10,18,54). Some elongation factors, including TFIIS (34) and Spt5 (36, 51), also bind the body of Pol II.The gene encoding Spt5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 91 publications
(162 reference statements)
8
51
0
Order By: Relevance
“…Considering this, along with the fact that Spt6 interacts with Spt5 (54), it is possible that Bur1 contributes in Spt6 recruitment through Spt5-CTR phosphorylation. However, an earlier study (54) showed that deleting Spt5-CTR did not impair Spt5-Spt6 interaction and, more recently, it was reported that Spt5-CTR did not significantly reduce Spt6 binding in vivo (56). Although the role of phospho-CTR in Spt6 recruitment cannot be ruled out, these studies, along with our results, strongly suggest that Bur1, together with Ctk1, promote Spt6 recruitment in a phosphorylated Ser2-dependent manner.…”
Section: Discussionsupporting
confidence: 52%
“…Considering this, along with the fact that Spt6 interacts with Spt5 (54), it is possible that Bur1 contributes in Spt6 recruitment through Spt5-CTR phosphorylation. However, an earlier study (54) showed that deleting Spt5-CTR did not impair Spt5-Spt6 interaction and, more recently, it was reported that Spt5-CTR did not significantly reduce Spt6 binding in vivo (56). Although the role of phospho-CTR in Spt6 recruitment cannot be ruled out, these studies, along with our results, strongly suggest that Bur1, together with Ctk1, promote Spt6 recruitment in a phosphorylated Ser2-dependent manner.…”
Section: Discussionsupporting
confidence: 52%
“…In vitro, Spt5 binds and activates the human capping enzyme (37), and its C-terminal repeat region (CTR) binds S. pombe triphosphatase and guanylyltransferase (38,40). To test whether Spt5 is involved in recruiting capping enzymes in vivo, we carried out ChIP analysis in S. cerevisiae strains expressing only Spt5 lacking the CTR (50,51). We detected a decrease in the occupancy of Cet1, Ceg1, and Abd1 to about 65%, 50%, and 35% of wild-type levels, respectively, at the 5= region of the ADH1 gene, whereas Pol II occupancy was relatively unaffected (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We carried out a correlation analysis with genome-wide occupancy profiles reported here and elsewhere (21,23,51). Pearson correlation coefficients between profiles were provided as a similarity metric to calculate a correlation-based two-dimensional network using the GraphViz's Neato algorithm (49).…”
Section: Figmentioning
confidence: 99%
“…Despite well-supported genetic and functional studies that implicate Spt4-Spt5 in transcription-coupled processes ranging from chromatin modification and RNA processing (5) to 3=-end formation (74)(75)(76), not much is known about how Spt4-Spt5 interacts with the RNAP ternary complex to function in these nuclear processes. Mechanistic understanding is limited to an NA encirclement model based on the binding of the Spt5 NGN domain to the RNAP Clamp module (26,27,34) and a general understanding of the Spt5 KOW domains' involvement in binding RNAP (11,17,59).…”
Section: Discussionmentioning
confidence: 99%